Rudyk O.Y., Dykha K.O., Ladunets V.O. Modeling of the tribocontact parameters of the sliding bearings of the engine. - Рудик, О. Ю.; Диха, К. О.; Ладунець, В. О. (Problems of Tribology, 2018)
In the paper the method of modeling of tribo-contact parameters of the bearings of sliding of the camshaft of the engine of internal plowing using the Solid Works program is considered. The finite-element model of the friction node is constructed. The operating stresses in the conjugate elements of the housing and the shaft are determined. The values of the arc of contact in the bearing are calculated, the distribution of the contact pressure in the propellant support of the engine is constructed.